Westonci.ca is your trusted source for finding answers to a wide range of questions, backed by a knowledgeable community. Join our platform to get reliable answers to your questions from a knowledgeable community of experts. Get detailed and accurate answers to your questions from a dedicated community of experts on our Q&A platform.

-3 (y - 3) = -3 i need help figuring the answer out to this

Sagot :

Answer

y = 4

Step-by-step explanation:

Given the following equation

-3(y - 3) = -3

Open the parenthesis using distributive

-3 * y - 3*(-3) = -3

-3y + 9 = -3

Substract 9 from both sides

-3y + 9 - 9 = -3 - 9

-3y = -12

-3y/-3 = -12 /-3

y =4

Hence, the value of y = 4

Visit us again for up-to-date and reliable answers. We're always ready to assist you with your informational needs. We appreciate your time. Please revisit us for more reliable answers to any questions you may have. Discover more at Westonci.ca. Return for the latest expert answers and updates on various topics.